How do health problems affect the quality and everyday life of patients with endometriomas? - K. Chmaj-Wierzchowska; M. Wojciechowska; I. Parda; K. Plagens-Rotman; P. Rzymski; M. Wilczak (Clinical and Experimental Obstetrics & Gynecology)
Introduction: The quality of human life is a subjective value and it largely depends on mental health, personality traits, preferences, and value system. This study aimed to discuss the incidence of health problems in patients with benign changes of reproductive organs (due to changes in the adnexa with the characteristics of endometrial cysts - endometriomas and other gynecological diseases, i.e. uterine myomas, other benign ovarian tumors), and influence of these problems with the daily functioning of the surveyed women. Materials and Methods: The study included patients treated surgically, due to changes in the adnexa with the characteristics of endometrial cysts (n = 24), other gynecological diseases (n = 45), i.e. uterine myomas (n = 22) and other benign ovarian tumors (n = 23) in 2017. The control group consisted of healthy patients (n = 67) who underwent routine, annual gynecological visits at the outpatient gynecological clinic, without changes within the reproductive organ (confirmed by using intravaginal ultrasound examination). The study research tool consisted of a questionnaire that was developed specifically for this study and the Nottingham Health Profile Questionnaire (NHP). The patients filled the questionnaires independently, one day prior to the procedure and in the control group prior to routine, annual doctor’s visit. Results: Among patients with endometriosis, significantly higher intensity of pain, emotional reactions, physical mobility, and vital energy were found. Women with endometrial cysts significantly more frequently reported issues related to occupation (Cramer’s V 0.578, p ≤ 0.001), household chores (Cramer’s V 0.597, p ≤ 0.001), social life (Cramer’s V 0.581, p ≤ 0.001), family life (Cramer’s V 0.576, p ≤ 0.001), sexual life (Cramer’s V 0.561; p ≤ 0.001), participation in hobbies (Cramer’s V 0.876, p ≤ 0.001), and holidays (Cramer’s V 0.876; p ≤ 0.001). Conclusions: Among patients with endometriosis a significantly higher intensity of pain, emotional reactions, physical mobility and energy vital. Because the advancement of endometriosis does not correlate with subjective complaints, routine use of Nottingham Heath Profile Questionnaire in the patients with endometriosis may improve the assessment of the severity of the disease and evaluate the effectiveness of treatment in the future.